2021
DOI: 10.3390/genes12091393
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Long Non-Coding RNA (lncRNA) in Mediterranean Mussel (Mytilus galloprovincialis) Hemocytes under Immune Stimuli

Abstract: The Mediterranean mussel is one of the most economically relevant bivalve mollusk species in Europe and China. The absence of massive mortalities and their resistance to pathogens affecting other cultured bivalves has been under study in recent years. The transcriptome response of this species to different immune stimuli has been extensively studied, and even the complexity of its genome, which has recently been sequenced, has been suggested as one of the factors contributing to this resistance. However, studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 72 publications
1
12
0
Order By: Relevance
“…It was suggested that these differentially expressed lncRNAs may shape the phenotypic plasticity of abalone by regulating the expression of genes involved in signal transduction, autophagy and apoptosis, and hormone regulation. So far, a lot of lncRNAs have been identified and classified in mammals and plants, , and there is also information available regarding the involvement of lncRNAs in fish, , mollusks, and other marine invertebrates under certain environmental conditions. However, the exact function identification of lncRNAs in these non-model animals requires more efforts and breakthroughs in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that these differentially expressed lncRNAs may shape the phenotypic plasticity of abalone by regulating the expression of genes involved in signal transduction, autophagy and apoptosis, and hormone regulation. So far, a lot of lncRNAs have been identified and classified in mammals and plants, , and there is also information available regarding the involvement of lncRNAs in fish, , mollusks, and other marine invertebrates under certain environmental conditions. However, the exact function identification of lncRNAs in these non-model animals requires more efforts and breakthroughs in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Other ncRNAs, including miRNAs and snRNAs, were identified by searching against the Rfam database with default parameters using the infernal software (http://infernal.janelia.org/). Additionally, lncRNAs were identified using the pipelines previously proposed (Gallardo-Escarate, Figueras, & Novoa, 2019; Pereiro et al, 2021; Tarifeno-Saldivia, Valenzuela-Miranda, & Gallardo-Escarate, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, lncRNAs were identified using the pipelines previously proposed (Gallardo-Escarate, Figueras, & Novoa, 2019;Pereiro et al, 2021;Tarifeno-Saldivia, Valenzuela-Miranda, & Gallardo-Escarate, 2017).…”
Section: Genome Annotation Of M Chilensismentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNAs are predicted to be important functions in the response to environmental stressors and regulate body growth in mollusks including exoskeleton biomineralization. For example, differential LncRNA expression profiles reveal the regulatory roles of LncRNAs in the against viruses and bacteria immune response of abalones, oysters, and mussels via links to multiple immune-related pathways, for instance, the toll-like receptor, NF-kappaB signaling pathway, pattern recognition receptors, lectin immune-related pathways, fibrinogen, and O-glycan biosynthesis (Sun and Feng, 2018;Lu et al, 2021;Pereiro et al, 2021). Also, LncRNAs are reported to participate in controlling shell formation and body growth by affecting pigmentation, shell matrix gene expression, and glycogen accumulation (Sun and Feng, 2018).…”
Section: Introductionmentioning
confidence: 99%